Postoperative granuloma after stapedectomy: Is it destiny or avoidable? - (:unkn) unknown (KARGER, 2007)
Objective: The aims of this study were (1) to investigate the pathophysiological characteristics of the middle ear mucoperiosteum against the caustic nature of the gastric content (GC), which consists largely of acid and pepsin components, and (2) to investigate the possible role of gastroesophageal reflux and postoperative vomiting (POV) in the etiology of poststapedectomy granuloma. Methods: 40 Spraque-Dawley rats of either sex and with a body weight of 200-300 g were used, and divided into different study groups: group 1: GC administration to the middle ear (n = 8); group 2: phosphate-buffered saline administration to the middle ear (n = 8); group 3: GC (pH: 2) administration in the presence of a Teflon piston (TP) (n = 6); group 4: phosphate-buffered saline administration in the presence of a TP (n = 6); group 5: GC administration in the presence of a wired piston (WP) (n = 6); group 6: phosphate-buffered saline administration in the presence of a WP (n = 6). GC was administrated to the middle ear cavities by way of the eustachian tube (ET). In order to overcome the pressure of the ET, a pump mechanism was used. The increased nasopharyngeal pressure caused a passive opening of the ET, and transferred a bolus to the middle ear. The animals were decapitated after I week, and the bullae were isolated. The tympanic bullae were serially cut and examined with light microscopy. Results: In the saline controls, there was only a mild amount of polymorphonuclear cell (PMN) infiltration in the mildly thickened subepithelial space, indicating a less pronounced inflammation as compared to the gastric acid group. In the GC group, in addition to focal hemorrhage and severe subepithelial infiltration of PMNs, the middle ear mucosa was dramatically thickened with subepithelial edema and dilated capillaries. In the subepithelial tissue, retention cysts and granulation tissue were present. In the piston groups (TP and WP), there was extensive subepithelial inflammation and edema after GC and saline administrations. Granulation tissue filling the entire bulla around the piston segments was detected. Conclusion: The relationship between the administration of GC and middle ear inflammation, and the possible role of POV in the etiology of poststapedectomy granuloma are emphasized with our experimental study. The length of the TP may be considerably important to prevent POV which may lead to gastric reflux to the middle ear. Copyright (c) 2007 S. Karger AG, Basel
Keywords: MIDDLE-EAR MUCOSA; REPARATIVE GRANULOMA; OTITIS-MEDIA; RAT; PREVENTION; NAUSEA